A low-fat yoghurt supplemented with a rooster comb extract on muscle joint function in adults with mild knee pain: a randomized, double blind, parallel, placebo-controlled, clinical trial of efficacy. Issue 11 (24th August 2015) - Solà, Rosa; Valls, Rosa-Maria; Martorell, Isabel; Giralt, Montserrat; Pedret, Anna; Taltavull, Núria; Romeu, Marta; Rodríguez, Àurea; Moriña, David; Lopez de Frutos, Victor; Montero, Manuel; Casajuana, Maria-Carmen; et al.
Abstract : Preliminary associations of RCE with improved muscle strength. Abstract : Preliminary results suggested that oral-administration of rooster comb extract (RCE) rich in hyaluronic acid (HA) was associated with improved muscle strength. Following these promising results, the objective of the present study was to evaluate the effect of low-fat yoghurt supplemented with RCE rich in HA on muscle function in adults with mild knee pain; a symptom of early osteoarthritis. Participants ( n = 40) received low-fat yoghurt (125 mL d −1 ) supplemented with 80 mg d −1 of RCE and the placebo group ( n = 40) consumed the same yoghurt without the RCE, in a randomized, controlled, double-blind, parallel trial over 12 weeks. Using an isokinetic dynamometer (Biodex System 4), RCE consumption, compared to control, increased the affected knee peak torque, total work and mean power at 180° s −1, at least 11% in men ( p < 0.05) with no differences in women. No dietary differences were noted. These results suggest that long-term consumption of low-fat yoghurt supplemented with RCE could be a dietary tool to improve muscle strength in men, associated with possible clinical significance. However, further studies are needed to elucidate reasons for these sex difference responses observed, and may provide further insight into muscle function.